The Effect of Health Education on Arv Therapy Adherence to Odha in The Ponggok Blitar Health Center Area - Ahmad Wasis Setyadi; Erna Irawati (CV. AFDIFAL MAJU BERKAH, 2026)
Adherence to Antiretroviral therapy (ARV) in People with HIV/AIDS (ODHA) is an important factor in suppressing viral replication and improving patients' quality of life. However, compliance is often low due to a lack of understanding and motivation. Health education is seen as an effective strategy to improve patient adherence to ARV therapy. This study uses a pre-experimental design with a one-group pre-test and post-test design. The research sample of 44 ODHA respondents was selected using a simple random sampling technique. Interventions in the form of health education about HIV/AIDS, the importance of ARV therapy, the benefits of adherence, and the risk of non-compliance were provided through interactive counseling. Data were analyzed using the Wilcoxon Signed Ranks Test to see differences in compliance before and after education. Before the intervention, all respondents (100%) were in the low compliance category. After the intervention, most respondents (86.4%) improved to moderate adherence. The results of the Wilcoxon test showed that none of the respondents experienced a decrease in compliance (negative ranks = 0), all respondents (positive ranks = 44) experienced an increase, with a value of Z = -6.289 and a p-value = 0.000 (p < 0.05). The results of the study prove that health education has a significant influence on increasing ARV therapy adherence in ODHA. Comprehensive education is able to increase knowledge, awareness, and motivation of patients to be more consistent in undergoing therapy. Thus, health education needs to be used as a routine intervention in HIV/AIDS control programs in primary services.